2017
DOI: 10.1177/1747493017744464
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of alteplase for acute stroke according to criteria defining the European Union and United States marketing authorizations: Individual-patient-data meta-analysis of randomized trials

Abstract: Background: The recommended maximum age and time window for intravenous alteplase treatment of acute ischemic stroke differs between the Europe Union and United States. Aims:We compared the effects of alteplase in cohorts defined by the current Europe Union or United States marketing approval labels, and by hypothetical revisions of the labels that would remove the Europe Union upper age limit or extend the United States treatment time window to 4.5 h. Methods: We assessed outcomes in an individual-patient-dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
44
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 20 publications
(31 reference statements)
0
44
0
1
Order By: Relevance
“… 6 , 21 , 23 25 , 27 Data were evaluated using statistical methods and outcomes similar to those described previously. 1 , 28 , 29 …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“… 6 , 21 , 23 25 , 27 Data were evaluated using statistical methods and outcomes similar to those described previously. 1 , 28 , 29 …”
Section: Methodsmentioning
confidence: 99%
“…However, key aspects of its regulatory approval differ by region. 1 For example, no upper age limit is stated in the US product label, but treatment must be initiated within 3 hours of stroke onset. 2 Alteplase is approved for use in Europe within 4.5 hours of stroke onset but, until recently, regulatory criteria restricted its use to patients aged 18–80 years.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Meta-analyses of pivotal randomized trials confirmed the benefit of intravenous thrombolysis (IVT) and mechanical thrombectomy (MT) in patients with acute ischemic stroke. 1,2 In addition to the treatment effect, the cost saved with the efficacyproven therapy should be considered in healthcare policy making for resource allocation and reimbursement. Earlier studies have already shown that IVT and MT are clearly cost-effective, but the magnitude of cost saving likely differs according to individual healthcare systems.…”
mentioning
confidence: 99%